1989
DOI: 10.1111/j.1365-2885.1989.tb00660.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and cardio‐respiratory effects of oral theophylline in exercised horses

Abstract: The pharmacokinetics of theophylline at rest and the effects on cardio-respiratory and blood lactate responses to exercise were investigated after repeated oral administrations in six healthy Standardbred horses. A dose of 5 mg/kg body weight was administered every 12 h. The binding of theophylline to plasma protein was also determined. There was good agreement between predicted and observed plasma concentrations of theophylline at steady state. The mean half-life of elimination was shown to be 17.0 +/- 2.5 h,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
1

Year Published

1991
1991
2010
2010

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
(12 reference statements)
0
6
1
Order By: Relevance
“…The absorption rate found for granulated theophylline (t 1/2hl = 0. Although the microencapsulated preparation was absorbed more slowly than the reference preparation, the t1/2hl (0.62 h) was faster in this study than that reported for controlled-release theophylline tablets (1.6 h - Ingvast-Larsson et al 1989;1.24 h -Errecalde and Landoni 1992).…”
contrasting
confidence: 56%
See 1 more Smart Citation
“…The absorption rate found for granulated theophylline (t 1/2hl = 0. Although the microencapsulated preparation was absorbed more slowly than the reference preparation, the t1/2hl (0.62 h) was faster in this study than that reported for controlled-release theophylline tablets (1.6 h - Ingvast-Larsson et al 1989;1.24 h -Errecalde and Landoni 1992).…”
contrasting
confidence: 56%
“…Repeated oral dosing resulted in theophylline trough-peak serum concentrations always greater (30%) than those predicted by the superimposition method; these findings are at variance with those published by Button et al (1985), who recorded plasma concentrations in treated animals that were always lower than predicted. On the other hand, experimental data by Ingvast-Larsson et al (1989) confirmed higher trough concentrations in treated animals than the 9 pdml as minimum effective concentration arrived at choosing 5 mg/kg bwt administered twice a day as the scheduled dosage. It is well known that repeated administrations give rise to smaller volume of distribution and higher peak concentration than obtained with a single administration (Ritschel 1992).…”
mentioning
confidence: 94%
“…Thus, the drug’s concentrations required to relax the tissues should be adequate to act on the enzymes. As evidenced by the pIC 50 values here obtained, the concentrations of theophylline required to relax the gastrointestinal regions are higher the ones achieved in plasma following in vivo administration of the drug in several animal species [44–46], the rabbit included [47–49]. Interestingly, this is also the case for the in vitro mean effective concentrations of theophylline required to produce bronchodilation in horses [10], dogs [11,12], cats [50], pigs [13], as well as in man [14,51].…”
Section: Discussionmentioning
confidence: 62%
“…T h e obtained corrected concentrations of unbound theophylline in the blood are in good accordance with the concentration obtained in plasma, when protein binding was taken into account. T h e protein binding determined in vitro in rat was about 50% at a concentration of 45 pg/ml (Okazaki et al, 1987) and in the horse 12% at concentrations of 5-60 @ml (Ingvast-Larsson et al, 1989). T h e data for in v i m protein binding (17.5%) a preliminary thin layer chromatography evaluation of the radioactivity in water-and ethylether-extracts from the lungs of one of the rats 20 min after injection of labelled theophylline indicates the presence of a labelled metabolite with an Rfvalue different from the parent compound.…”
Section: Disc Ussl Onmentioning
confidence: 99%